Building Better Cities: Evaluating the Effect of Circular Economy City Construction on Air Quality via a Quasi-Natural Experiment. (13th September 2022) - Zhu, Yanjiao; Mao, Chunmei; Jia, Qiong; Barnes, Stuart J.; Yao, Qing
Abstract : The resource utilization of a circular economy should reflect both economic and environmental values. Resource utility can be measured by GDP in the short term, while environmental value is challenging to measure; that is, the improvement in air quality is not effectively evaluated. In order to examine this initiative, using China's pilot cities of circular economy as a quasi-natural experiment, we construct a difference-in-difference (DID) strategy for estimation. The results demonstrate the following: (1) the pollutant emissions of pilot cities decline by 2.92 percentage points (p < 0.01 ) compared to unpiloted cities, (2) the policies on pilot cities more rapidly enhanced air quality for central cities and those with a low level of economic development, and (3) pilot cities significantly enhance air quality by decreasing energy consumption per unit of GDP. We provide the first empirical evidence of the effectiveness of circular economy pilot cities in improving air quality.